2012
DOI: 10.1007/s10310-011-0303-4
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific variation in leaf water use associated with drought tolerance in four emergent dipterocarp species of a tropical rain forest in Borneo

Abstract: By use of tree-tower and canopy-crane systems we studied variations in the water use, including transpiration, stomatal conductance, and leaf water potential, of the uppermost sun-exposed canopy leaves of four emergent dipterocarp species in an aseasonal tropical rain forest in Sarawak, Malaysia. Midday depression in stomatal conductance and leaf water potential was observed in all the species studied. Interspecific differences were clearly observed in the maxima of transpiration rates and stomatal conductance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 66 publications
(83 reference statements)
1
16
0
Order By: Relevance
“…Lamarre et al (2014) suggested that leaf flushing phenology in tropical rain forest trees might be closely related to soil resource availability; some species growing in poor soil under frequent drought stress might be favored to produce a large number of leaves all at once, which might represent lower cost than to produce leaves continuously. However, it seems that the species studied did not reflect any soil resource availability for their leaf flushing phenology, because they bore little relation to soil texture; species distributed over sandy soil, such as DrA, SB and DG, showed various leaf flushing patterns, and the same goes for those distributed over clay soil, such as DP and SF (Itoh 1995, Hirai et al 1997, Hiromi et al 2012, Lee et al 2002, Ashton 2004.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Lamarre et al (2014) suggested that leaf flushing phenology in tropical rain forest trees might be closely related to soil resource availability; some species growing in poor soil under frequent drought stress might be favored to produce a large number of leaves all at once, which might represent lower cost than to produce leaves continuously. However, it seems that the species studied did not reflect any soil resource availability for their leaf flushing phenology, because they bore little relation to soil texture; species distributed over sandy soil, such as DrA, SB and DG, showed various leaf flushing patterns, and the same goes for those distributed over clay soil, such as DP and SF (Itoh 1995, Hirai et al 1997, Hiromi et al 2012, Lee et al 2002, Ashton 2004.…”
Section: Discussionmentioning
confidence: 98%
“…All the species are evergreen and dominate the canopy and emergent layers in the study sites (Table 1). DG, DrA and SB are distributed over sandy soil and, DP and SF over clay soil (Itoh 1995, Hirai et al 1997, Hiromi et al 2012, Lee et al 2002, Ashton 2004 (Table 1). But the distribution of these dipterocarp species is unrelated to soil pH (Lee et al 2002).…”
Section: Study Speciesmentioning
confidence: 94%
“…Species with high wood density have a different strategy to cope with severe drought compared to stem succulent species, as they have a thicker cell wall and/or narrower conduits providing a high resistance to xylem embolism (air bubbles breaking the water column) [43]. For instance, tree species with high wood density were able to survive the severe drought event induced by the strong 1997-1998 El Niño whereas high mortality rate was observed in lower wood density species in Bornean tropical rainforest [62]. Furthermore, the size of DDF species has no effect on wood density, except S. obtusa Wall.…”
Section: Discussionmentioning
confidence: 99%
“…We also conducted paired t-tests to determine the differences in wood traits of five tree species with high wood density were able to survive the severe drought event during 1997-1998 El Niño as compared with lower wood density species in Bornean tropical rainforest (Bebber 2000, Hiromi et al 2012. Further large datasets on community-level wood density and water content from broad climate zones in tropical Southeast Asia are needed to clarify the precise relationship between wood traits and environmental conditions, especially for precipitation and dry spell length.…”
Section: Discussionmentioning
confidence: 99%
“…The traits of stem woody parts, namely wood density and water content, have a strong relationship with their functional traits, such as drought tolerance, crown architecture, growth rate, survival, and photosynthesis, especially in tropical forests (Bucci et al 2004, Hiromi et al 2012, Inoue et al 2015, Ishida et al 2008, Kenzo et al 2011, Markesteijn et al 2011, Martin et al 2013, Santiago et al 2004. For example, trees with low wood density exhibit a faster growth rate compared with trees of high wood density, whereas trees with high wood density usually have a high survival rate due to their stronger resistance to physical stress, pathogens, and pest attacks (Curran et al 2008, King et al 2005, 2006, Kitajima 1994.…”
Section: Comparison Of Wood Density and Water Content Between Dry Evementioning
confidence: 99%